Diamonds from the Coromandel Area, West Minas Gerais State, Brazil: an update and new data on surface sources and origin - Joachim Karfunkel; Donald Hoover; Augusto Fonseca Fernandes; Geraldo Norberto Chaves Sgarbi; Klaus Kambrock; Gustavo Diniz Oliveira (Brazilian Journal of Geology)
Important diamond deposits southeast of Coromandel and the local geology have been studied in an attempt to understand what surface source provided the stones. River gravels of Pleistocene to Recent age from this region have supplied most of Brazil's large diamonds over 100 ct. The upper cretaceous Capacete Formation of the Mata da Corda Group, composed of mafic volcanoclastic, pyroclastic and epiclastic material, has been worked locally for diamonds, nevertheless considered non-economic. The authors present results of their study of a deactivated small mine, representing the first report with description and analyses of two gem diamonds washed from this material. Hundreds of kimberlites, discovered in the last half century in the region, are sterile or non-economic. We propose that the surface source of the diamonds is the Capacete "conglomerado". The volume of this material is enormous representing a potential resource for large-scale mining. The authors suggest detailed studies of the volcanic facies of this unit focusing on the genesis, distribution and diamond content. As to the question concerning the origin of these diamondiferous pyroclastic rocks, the authors exclude the kimberlites and point towards the large Serra Negra and Salitre alkaline complexes which are considered the primary source for the pyroclastic units of the Mata da Corda Group. They propose that early eruptive phases of this alkaline complex brought diamonds from a mantle source to the surface, much as happens with traditional kimberlites, to explain the association of such huge carbonatite complexes and diamonds.